Pertumbuhan Tanaman Sengon Rotasi Ke- 2 Asal Trubusan Umur Tahun di Widodomartani, Ngemplak, Sleman, Yogyakarta - Prijono, Agus; Saputro, Setiaji Heri (Jurnal Wana Tropika, 2025)
The Widodomartani community cultivates some of their land for forest plants, generally sengon  is liked community because fast growing species and harvested quickly. Generally, the planting used is seedling, for efisiensi budgeting tried with coppice sistem. This research aims to determine the growth of second rotation at the age 1-years old sengon with coppice sistem. The growth data taken is sum coppice at every sengon, and height, diameter for each coppice at individual sengon. The results research showed that coppice after first rotation used seedling at the age 1-years old sengon there is a tendency that the larger the diameter of the stump or stump, the more shoots there are. The growth of sengon (Falcataria moluccana) plants in the second rotation, aged 1 year, originating from coppice shoots (coppice system) from a 5 years old stand, with an average height of 5.193–7.596 m and an average diameter of 3.396–5.656 cm per shoot, showed better results than sengon growth in the first rotation. The disturbance found was tumor rust caused by Uromycladium tepperianum.